Penerapan Keselamatan dan Kesehatan Kerja (K3) dalam Kegiatan Intrakurikuler Sekolah Menengah Kejuruan - Sigit Widianto; Nurtanio Agus Purwanto (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The purpose of this research is to describe the school conditions in terms of Occupational Safety and Health (OSH) principles. In the schools, learning about Occupational Safety and Health (OSH) includes both theoretical and practical aspects. This study employed a qualitative descriptive method, conducted at Vocational high school of Mitra Industri MM2100 Bekasi Regency, Vocational high school of Mitra Industri Putra Darma Bekasi Regency, and Vocational high school of Mitra Industri 02 Pati. Subjects included school principals, supporting informants, Occupational Safety and Health (OSH) trainers, and the Head of Industrial Relations Division. The Data were found by observation, interviews, and documentation. The result of the research is used Miles and Hubberman's theory, which involves data reduction, data presentation, and conclusion drawing/verification. This study showed that schools have made efforts to increase students' awareness of Occupational Safety and Health (OSH), including: (1) Planning implementation of Occupational Safety and Health (OSH) principles in the school environment (2) Planned training, such as safety riding to minimize accidents on the road, and the importance of safety dojo training to raise students' awareness of Occupational Safety and Health (OSH). (3) Supporting factors in Occupational Safety and Health (OSH) learning at school include a culture and environment to industrial standards, although implementation may differ between industry and school regulations. As a result of implementing OSH culture, students can easily and effectively absorb it during the learning process.